The Silencing of Women in Marlina: The Murderer in Four Acts - Ndari, Yunni Wulan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Today, violence against women is becoming a globally important issue. This is inseparable from the record of cases that continue to increase every year, not least in Indonesia. The recorded numbers are like an iceberg phenomenon that only some victims dare to report. There are still many cases that have not been revealed. Violence against women also varies in types, not only limited to physical violence but also verbal to sexual violence. As one part of the mass media, film is a powerful mass communication media in conveying judgments or general images of many things. . Films are considered to have the ability to shape public opinion including people's perception of male dominance in the social order. One of the films that represents this is Marlina: The Murderer in Four Acts. Marlina: The Murderer in Four Acts has a uniqueness in the delivery of messages that are rarely found in films made by domestic filmmakers. Taking place in Sumba Regency, East Nusa Tenggara, the film depicts how Marlina was sexually, physically and verbally assaulted. The severity of this violence was done while she was grieving the death of her husband. This film reaffirms to all of us that women are the liyans of male oppression. Even as women defended the violence that befell them, women were again discredited for the existing system.